Breastfeeding transition in Oman: A generation shift or a product of social development? A qualitative study on three generations of Omani mothers - Atika Khalaf; Rebecca Mathew; Pernilla Ny (PLoS ONE, 2025)
Background Exclusive breastfeeding is essential for infant health, yet its practice varies across generations and cultures. Although the health benefits of breastfeeding have been well known for decades, the utilization of infant formula feeding worldwide and in Oman, in particular, continues to rise, most likely as a result of a lack of social support and the time limit faced by working mothers. Little is known about the factors affecting Omani mothers’ breastfeeding experiences and practices. Therefore, this study aims to gain an in-depth understanding of the experiences of breastfeeding practices among three generations of Omani mothers. Methods This qualitative study investigated exclusive breastfeeding practices among three generations of Omani mothers. Participants were recruited using a selective approach followed by a snowball technique, resulting in a total of 50 women, which included 17 first-generation mothers, 18 grandmothers, and 15 great-grandmothers. Participants were characterized by varying ages and socio-demographic backgrounds. Semi-structured face-to-face interviews were conducted in Arabic, and data collection continued until data saturation was reached. Data were analyzed using qualitative content analysis methodology, ensuring robustness and credibility. Results The analysis yielded two main categories reflecting the mothers’ experiences, three representing the grandmothers’ experiences, and two concerning the great-grandmothers’ experiences. While overarching themes like the significance of breastfeeding emerged across all generations, disparities were seen concerning challenges, beliefs, and support systems. Mothers highlighted contemporary hurdles such as work-life balance and societal pressures, whereas grandmothers emphasized inherited practices and cultural norms. Great-grandmothers reflected on the evolution of societal and familial dynamics impacting breastfeeding traditions. Despite these differences, a shared commitment to breastfeeding and recognition of its importance for maternal and child well-being was evident across generations. Conclusion The findings underscore the importance of societal support, healthcare provider education, and workplace policies in promoting exclusive breastfeeding. Targeted interventions are needed to address barriers to breastfeeding and empower women to make informed feeding choices. By addressing these challenges, societal institutions can contribute to achieving higher rates of exclusive breastfeeding and improve maternal and child health outcomes in Oman.